If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(k + -2) + -4(m + 3) = 0 Reorder the terms: 5(-2 + k) + -4(m + 3) = 0 (-2 * 5 + k * 5) + -4(m + 3) = 0 (-10 + 5k) + -4(m + 3) = 0 Reorder the terms: -10 + 5k + -4(3 + m) = 0 -10 + 5k + (3 * -4 + m * -4) = 0 -10 + 5k + (-12 + -4m) = 0 Reorder the terms: -10 + -12 + 5k + -4m = 0 Combine like terms: -10 + -12 = -22 -22 + 5k + -4m = 0 Solving -22 + 5k + -4m = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '22' to each side of the equation. -22 + 5k + 22 + -4m = 0 + 22 Reorder the terms: -22 + 22 + 5k + -4m = 0 + 22 Combine like terms: -22 + 22 = 0 0 + 5k + -4m = 0 + 22 5k + -4m = 0 + 22 Combine like terms: 0 + 22 = 22 5k + -4m = 22 Add '4m' to each side of the equation. 5k + -4m + 4m = 22 + 4m Combine like terms: -4m + 4m = 0 5k + 0 = 22 + 4m 5k = 22 + 4m Divide each side by '5'. k = 4.4 + 0.8m Simplifying k = 4.4 + 0.8m
| 2(2x+.33)=.5(x+5.33) | | -8.5+4.7=328.55 | | 9/15=3x/10 | | 16x^2-121x+576=0 | | 9x-15y=8 | | y=15-.025x | | 7/10=×/50 | | 5x=4(10x) | | 2x+6=-5x+3 | | 4x+40=-20 | | x-2(x+3y)-(2x+3y)-4(x+y)= | | 5x+8=14-3x | | 10x-15=5(2+3x) | | -12=5b/8 | | 4(8n+2)=40 | | -0.9y+8.5=43.6 | | 9x+-2=43 | | 16x^4+8x^3=0 | | 10/2.4=p/2.64 | | -6n+10=46 | | 3(4+3r)=18 | | -2x(x-3)+4x=-(-x+1) | | (-8a)(-3/4) | | R/10=21/7 | | -48=7(7a+7)+3(8a-8) | | 1/9x-15=5 | | -6.9b+7.2=335.64 | | 47=3x+14 | | 2u+14=32 | | -2z^2=288 | | 19x-(18-5)=27 | | 18-5y=18 |